Is this pregnancy legitimate because it is (un)intended and (un)affordable? - Reuvers, Megan Joanne (Rhodes University, 2026)
The provision of social support during pregnancy is considered integral to positive mother and infant health and well-being. Research on the topic has been primarily quantitative and has demonstrated that higher levels of support mediate against poor mental well-being. However, its effects on physiological outcomes and maternal behaviours are less conclusive. Researchers suggest that these mixed findings point to how social support is measured, understood and perceived differently across social groups, socio-cultural settings and global regions. Qualitative studies generally describe the types and sources of social support provision but have not considered how such support is discursively constructed within power relations. Moreover, social support has been conceptualised in relation to immediate support networks, leaving support structures (socio-economic, -political, and -cultural norms and institutional structures) underexamined. Macleod’s pregnancy supportability framework expands on the notion of social support to include support structures. This framework conceptualises supportability as a “combination of a woman’s physiological, emotional and cognitive capacities to carry a pregnancy, which are enabled or constrained through the micro-level and macro-level ‘support’ that she receives”. Micro-level support refers to immediate support networks. Macro-level support relates to support structures; these include socio-cultural norms, discourses and practices and socio-economic and -political institutions and policies. The supportability framework has not, however, been operationalised methodologically. Using a reproductive justice approach and intersectionality theory, I sought to operationalise this framework qualitatively in this thesis. I argue that a positioning analysis informed by Sue Wilkinson’s and Celia Kitzinger’s approach to positioning theory and Patricia Hill Collins’ domains of power thesis could guide a supportability framework analysis. To demonstrate this, I conducted a multi-level analysis of the reported support interactions across the personal, micro-level and macro-level social contexts of pregnant women living in two towns in the Eastern Cape province of South Africa. A purposive sampling strategy was employed, recruiting participants over 18 years old, in their second trimester of pregnancy, and attending antenatal care. The rationale for operationalising the framework in this context stems from persistent reproductive disparities that affect the health and well-being of pregnant individuals in post-apartheid South Africa, especially for those who live in rural regions of the country. These inequalities persist despite a progressive rights-based policy environment and government commitments to addressing the social determinants of reproductive health. The supportability framework formed the template upon which 15 pregnant women’s photo-elicited supportability narratives were analysed. Each pregnancy story was diverse because the support interactions were highly context-specific. However, two interrelated macro injustices – norms surrounding socially (in)appropriate childbearing and structures underpinning socio-economic inequality – shaped participants’ discursive constructions of the supportability of their pregnancies. Participants constructed support as conditional and subject to deservingness based on their social positions in South African society. Participants attempted (and also struggled) to present as legitimate pregnant subjects by justifying their pregnancies given their social locations. The affordability of the pregnancy underpinned participants’ ability to present as responsible pregnant subjects and informed their reproductive autonomy in making decisions about their pregnancies. The findings demonstrate that “exemplary” childbearing is pinned on individual “choices” and behaviours but it is mostly unattainable because it is conditional on the micro and macro support environments that circumscribe it. These environments are imbued with coloniality, apartheid history, capitalism, socio-economic status, race, patriarchy, nationality, maturity and ability, which operate in concert to enable or, in most cases, hinder the supportability of pregnancies. My qualitative operationalisation of the supportability framework demonstrates that, despite a human rights-based policy framework, contextual systemic issues need considered attention in maternal health promotion. A biomedically-based antenatal care model is woefully inadequate in promoting the supportability of pregnancies. Multi-sectoral efforts such as addressing disrespectful maternity care, strengthening maternity social protections and addressing discriminatory labour practices are needed to enhance micro-level and macro-level support.
an intersectional analysis of pregnancy “supportability”
Keywords: Uncatalogued